The negotiation book your definitive guide to successful negotiating - Gates, Steve (Wiley, 2011)
"Negotiation is one of the most important skills in business. Fact. No other skill will give you a better chance of optimising your success and your organisation's success. Every time you negotiate, you are looking for an increased advantage. This book delivers it. From planning, dynamics and strategies, to psychology, tactics and behaviours, nothing will put you in a stronger position to build capability, build negotiation strategies and facilitate negotiations through to successful conclusions"--EBL.